Cytotoxicity of myrtenal on different human cancer cell lines (Annals of Medical Research, 2024)
Aim: Myrtenal (Myrt), a monoterpene found in essential oils of various plant species, such as Citrus aurantium, Citrus limon, Mentha japonica and Zingiber officinale roscoe. Preclinical studies have reported that Myrt induces apoptosis in various cancer models. This study aimed to investigate the effects of Myrt on cell viability in human prostate (LNCaP), colon (Caco-2), breast (MCF-7) and ovarian (A2780) cancer cell lines.Materials and Methods: A2780, LNCaP, MCF-7 and Caco-2 cell lines were used in this study. All cell lines were treated with 1, 5, 25, 50 and 100 μM concentrations of Myrt for 24 hours. Changes in cell viability were determined by the MTT assay. The inhibitory concentration 50 (IC50) and logIC50 values of Myrt in cell lines was calculated based on the cytotoxicity results.Results: Myrt concentrations applied to Caco-2, A2780, MCF-7 and LNCaP cancer cell lines for 24 hours significantly decreased cell viability (%) (p
Keywords: Myrtenal; Cancer; Cytotoxicity